Remyelinating strategies: What can be learned from normal brain development. (December 2022) - Shelestak, John; Irfan, Muhammad; DeSilva, Tara M.
Abstract: Multiple sclerosis (MS) is a neuroinflammatory demyelinating and neurodegenerative disease of the central nervous system (CNS). Immunomodulatory therapies are effective in reducing relapses, however, there is no remedy for progressive disease emphasizing the need for regenerative strategies. Chronic demyelination causes axonal injury and loss which is a key component of neurodegeneration and permanent disability in MS. New oligodendrocyte progenitor cells (OPCs) proliferate in response to inflammatory demyelination representing the potential for remyelination to protect axons and preserve neuronal function. The majority of remyelinating therapies have targeted intrinsic signaling processes in oligodendrocytes to promote differentiation or utilized methods for transplantation of oligodendrocytes. Here, we discuss specific roles of microglia in contributing to normal myelin development and the significance of these functions for remyelinating strategies.